Czy Tatarkiewicz doradcom filozoficznym jest do szczęścia potrzebny? = Do philosophical counselors need Tatarkiewicz to be happy? - Habura, Adrian (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper undertakes the task to present selected aspects of Władysław Tatarkiewicz`s conception of happiness contained in his book Analysis of Happiness. Consideration has been given to issues that seem to be significant from a philosophical-counseling perspective: the definition of happiness, the concept of human individual, and the relation of human individual to society and the world (subjective-objective feedback). The paper answers the question posed in the title only initially. A synthetic presentation of the content of selected chapters of the treatise has a dual purpose: on the one hand, the paper can be used to learn about selected issues raised by Tatarkiewicz in the treatise; on the other hand, it can be treated as auxiliary material to support the reading of the treatise.
Keywords: Tatarkiewicz, Władysław (filozof polski; 1886-1980); szczęście; człowiek; doradztwo filozoficzne; happiness; human; philosophical counseling